Servizi satellitari COPERNICUS e GALILEO - Agenzia Spaziale Italiana, ASI (Archeomatica, 2018)
ASI, the Italian Space Agency, is engaged with various national, European and international initiatives, in the transfer of technology and in the development of the downstream sector of applications based on satellite services such as Galileo and Copernicus. ArTeK is one of the projects funded by ASI within the ESA program "Business Applications", ESA's specific programme that promotes initiatives for the study, experimentation and prototyping of innovative services enabled by the various satellite services, today available such as earth observation, navigation and satellite telecommunications.